Life-threatening coronary vasospasm in patients with type 2 diabetes with SGLT2 inhibitor-induced euglycemic ketoacidosis: a report of two consecutive cases - Kawahara, Junko; Kaku, Bunji; Yagi, Kunimasa; Kitagawa, Naotaka; Yokoyama, Maki; Wakabayashi, Yusuke; Senda, Satoko; Takata, Hiroyuki; Hiraiwa, Yoshio (Diabetology international, 2024)
Euglycemic diabetic ketoacidosis (eDKA) has emerged as an adverse event associated with sodium-glucose transporter-2 inhibitors (SGLT2i). We present two consecutive cases of SGLT2i-induced eDKA, both manifested as life-threatening coronary vasospastic angina (VSA). Case 1: A 64-year-old male overweight patient with type 2 diabetes (BMI 28.2 kg/m 2 ), treated with dapagliflozin 5 mg daily for 6 months and a restricted diet for 2 months, experienced loss of consciousness following severe chest pain while driving, resulting in a traffic accident: plasma glucose, 163 mg/dL; urine ketones, (+++); bicarbonate (HCO 3 − ), 13.2 mmol/L; and total ketone body, 1539 µmol/L. Coronary angiography (CAG) performed on day 5 revealed diffusely spastic coronary arteries with 90% stenosis in the right coronary artery, leading to the diagnosis of VSA in the presence of coronary atherosclerosis. Case 2: A 63-year-old male patient with type 2 diabetes (BMI 22.2 kg/m 2 ) experienced severe chest discomfort and faintness following 2 months of chest pain while on dapagliflozin 10 mg daily for 1 year: plasma glucose, 112 mg/dL; urine ketones, (+++); HCO 3 − , 15.3 mmol/L; and total ketone body, 10,883 µmol/L. CAG performed on day 10 revealed no organic stenosis but diffusely spastic coronary arteries in response to coronary ergonovine infusion, confirming the diagnosis of VSA. SGLT2i has the potential to inhibit acetylcholine and butyrylcholine esterase activities, leading to reduced scavenging of acetylcholine and possible induction of coronary vasospasm. These cases highlight the association between life-threatening VSA and SGLT2i-induced eDKA.